Extensive lesions and a positive cone margin are strong predictors of residual disease in subsequent hysterectomy following conization for squamous intraepithelial lesion grade 2 or 3 study design - Hongfa Peng; Wencan Liu; Jingjing Jiang; Hui Du (BMC, 2023)
Abstract Background This study aimed to determine the predictive factors for post-conization of residual disease in subsequent hysterectomy for cervical intraepithelial neoplasia grade 2 or 3. Methods This retrospective study included 267 patients with histologically confirmed cervical intraepithelial neoplasia grade 2 or 3 who underwent hysterectomy within 7 months after conization. Clinical data (e.g., age, menopausal status, gravidity, parity, type of transformation zone, conization method) as well as pathological data pertaining to conization and hysterectomy were collected from medical records. A logistic regression model was used to analyze the relationship between the variables and risk of residual lesions in hysterectomy samples. Results Overall, 70 (26.2%) patients had residual lesions in their hysterectomy specimens. Univariate analyses revealed that age ≥ 50 years (p=0.019), endocervical gland involvement(p=0.013), positive margin(p < 0.001), and involvement of 3-4 quadrants(p < 0.001) were risk factors for residual lesions. Conversely, postmenopausal status, gravidity ≥ 3, parity ≥ 2, loop electrosurgical excision procedure, and type III transformation zone were not risk factors for residual lesions. A positive margin(p < 0.001) and multiple-quadrant involvement(p < 0.001) were identified as independent risk factors for residual lesions on multivariate analysis. Conclusions Multiple-quadrant involvement and a positive cone margin were reliable predictive factors for residual disease. Total hysterectomy or repeated cervical conization should be considered for patients with these two risk factors. The identification of high-risk patients with extensive lesions by colposcopic examination before conization is indispensable, as it will enable surgeons to perform conization with consideration of risk factors and possibly improve the approach used for the excisional procedure. For high-risk patients, colposcope-guided cold-knife conization is preferred when resources permit.